Meta-analysis of cooperative learning to improve learning outcomes in biology subject - aprilia, nani; isnaeni, bekti (Universitas Ahmad Dahlan, 2024)
This research aims to re-analyze the cooperative learning model to improve learning outcomes in Biology subjects. The cooperative learning model is an active learning model that focuses on group work, positive relationships, mutual cooperation, and motivating each other so that promotive interactions occur to create a learning community. This analytical research uses the meta-analysis method. The first stage of research is formulating the problem, followed by exploring existing relevant research for analysis. Data collection in this research used non-test techniques by searching through electronic journals Google Scholar, Researchgate and documentation studies in the library. There are forty-eight articles from journals and two from thesis collections found in the library. Based on the results of the analysis, it turns out that the cooperative learning model can improve student learning outcomes in Biology subjects.